Epidemiology of Infantile Spasms in Iceland ... - Millichap, J. Gordon (Pediatric Neurology Briefs Publishers, 1994)
Incidence, etiology, development, EEG, response to ACTH, and follow-up of all cases of infantile spasms diagnosed in Iceland during a 10-year period are reported from the National University Hospital, Reykjavik, Iceland, and Columbia University, New York. ...